PERAN MANAJEMEN KURIKULUM PENDIDIKAN TERHADAP MASA DEPAN BANGSA - Khabib Sharifudin (ADISAM PUBLISHER, 2024)
Education plays an important role in determining the existence of the nation in the future. Strategies that can realize the aspirations of the country are needed in the process of implementing education. Educational strategies will determine the direction and goals of education. One way is to use the educational curriculum as a standard to measure and adjust the needs of the labor market. Human resources born from the world of education with good curriculum management will provide maximum contribution to the labor market. The Faculty of Engineering, Padang State University monitors and evaluates the educational curriculum periodically. The Faculty of Electronic Engineering continues to strive to provide the best dedication to the nation. This is evidenced by the Electronic Engineering Faculty of Engineering, Padang State University by producing competent human resources in their fields. Each graduate is equipped with licensed competencies recognized by the state. A field survey has been conducted at the Department of Electronic Engineering, Faculty of Engineering, Padang State University when prospective alumni prepare their files to graduate. This is proof of the dedication of the Department of Electronic Engineering, Faculty of Engineering, Padang State University for the progress of the nation in the future